2020
DOI: 10.1021/acsanm.0c01326
|View full text |Cite
|
Sign up to set email alerts
|

Response of Human Blood Platelets on Nanoscale Groove Patterns: Implications for Platelet Storage

Abstract: Understanding platelet–surface activation is of clinical importance because it directly involves the formation of a hemostatic plug or blood clot at sites of vascular injury. Although platelet activation on various structured patterns has been investigated, this behavior on nanoscale groove patterns remains unclear. Here, we fabricated pattern arrays with 100 and 500 nm groove sizes by electron-beam lithography and investigated the response of platelets on these patterns using scanning electron microscopy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 44 publications
0
32
2
Order By: Relevance
“… 4 However, this film allows inhibiting platelets only up to ∼15 min, 4 or a bit longer on laminin-coated nanopatterns. 6 With agarose, a very low density of adhered platelets was observed, while we did not observe any changes in surface morphology of platelets up to 2 h of surface contact. Our present study clearly shows a potential application of the powerful agarose gel for the inhibition of platelet-surface activation as the agarose gel is easy to fabricate without the requirement of additional materials, highly stable, and extremely inert.…”
Section: Discussioncontrasting
confidence: 64%
“… 4 However, this film allows inhibiting platelets only up to ∼15 min, 4 or a bit longer on laminin-coated nanopatterns. 6 With agarose, a very low density of adhered platelets was observed, while we did not observe any changes in surface morphology of platelets up to 2 h of surface contact. Our present study clearly shows a potential application of the powerful agarose gel for the inhibition of platelet-surface activation as the agarose gel is easy to fabricate without the requirement of additional materials, highly stable, and extremely inert.…”
Section: Discussioncontrasting
confidence: 64%
“…Human blood from healthy donors who were drug-free within the previous 10 days was collected into a tube of ACD-A 1.5 mL BD-Vacutainer (Fresenius Kabi, Bad Homburg, Germany) as previously described [ 41 ]. The blood tube was sealed with parafilm and rested at room temperature for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…High anisotropy could guide cell contacts, this could lead to the activation process of platelet [ 59 ], activated platelets then attracts more adhesion of platelets. Another research from Bui et al [ 60 ] investigated the platelet adhesion and activation on grooved surface with 100 nm and 500 nm groove width. Results showed that 100 nm sample got a lower platelet adhesion and activation, which seems to conflict findings from Ding et al [ 57 ].…”
Section: Effects Of Topography and Surface Chemistry On Stentsmentioning
confidence: 99%
“…Secondly, 100 nm sample has much lower groove depth than 500 nm samples, this also reduce the guidance of groove structure. As a results of increase ligand density and decreased groove depth, the platelet adhesion and activation on 100 nm sample is lower than 500 nm sample [ 60 ].…”
Section: Effects Of Topography and Surface Chemistry On Stentsmentioning
confidence: 99%